Defect engineering of single- and few-layer MoS2 by swift heavy ion irradiation. (12th December 2016) - Madauß, Lukas; Ochedowski, Oliver; Lebius, Henning; Ban-d'Etat, Brigitte; Naylor, Carl H; Johnson, A T Charlie; Kotakoski, Jani; Schleberger, Marika
Abstract: We have investigated the possibility to use swift heavy ion irradiation for nano-structuring supported and freestanding ultra-thin MoS2 samples. Our comprehensive study of the ion-induced morphological changes in various MoS2 samples shows that depending on the irradiation parameters a multitude of extended defects can be fabricated. These range from chains of nano-hillocks in bulk-like MoS2, and foldings in single and bilayer MoS2, to unique nano-incisions in supported and freestanding single layers of MoS2 . Our data reveals that the primary mechanism responsible for the incisions in the ultrathin supported samples is the indirect heating by the SiO2 substrate. We thus conclude that an energy of less than 2 keV per nm track length is sufficient to fabricate nano-incisions in MoS2 which is compatible with the use of the smallest accelerators.